PENGARUH STRATEGI PENGEMBANGAN DOSEN PERGURUAN TINGGI DAN MOTIF BERPRESTASI TERHADAP PRODUKTIVITAS KERJANYA - Djuwita, Tita Meirina (2004)
This research is aimed at finding out the phenomenon and description of various aspects wich are related to Higher Educational Lecturer Development Strategy and Achievement Motivation, and to explain how great is the impact on lecturer productivity in Private Higher Education Coordination Region IV. Higher Educational Lecturer Development Strategy is analyzed through mission, goal, objective, value, planning, and analysis of environment, implementation, and evaluation. Achievement Motivation is analyzed through motivation and productivity, goal anticipate, problem solving ability, outcome respond. While lecturer work productivity is analyzed through not only just meeting the work qualification, high motivation, having positive work orientation, mature, effectively social interaction. The research method applied is explanatory survey and research data is obtained questioner as mayor technique, supplementing with interview, secondary data exploring rules and regulation, annual report, archives other document studies. The respondents were 123 lecturers Private Higher Education IV In West Java drawed through Stratified Random Sampling based on there employment status. The result shows that Higher Education Lecturer Development Strategy and Achievement motivation may be categories as approaching to high level status. The statistic shows that sub variable of higher education Lecturer development namely : objective, implementations, and evaluation bring about positive impact 50,9% to work productivity, sub variable achievement motivation namely : motivation and productivity bring about positive impact 54,5% to work productivity. The totally higher education lecturer development bring about positive impact 24,96 to work productivity. The totally achievement motivation bring about positive impact 24,96% to work productivity. Thus higher education development strategy and achievement motivation both bring about positive impact to Lecturer Productivity Private Higher Education Region IV 67,92%. Management of private Higher Education and Private Higher Education Coordination Region IV that are responsible to improve the productivity of Lecture in education and teaching, research and community services are recommended provide opportunity of further education (S2, S3) and training in line with field of study, increasing the need of achievement motivation and the need of community development.